Garden irrigation as household end-use in the presence of supplementary groundwater supply - Meyer, Bettina Elizabeth; Jacobs, Heinz Erasmus (Water S. A., 2019)
Garden irrigation is a significant and variable household water end-use, while groundwater abstraction may be a notable supplementary water source available in some serviced residential areas. Residential groundwater is abstracted by means of garden boreholes or well points and – in the study area – abstracted groundwater is typically used for garden irrigation. The volume irrigated per event is a function of event duration, frequency of application and flow rate, which in turn are dependent on numerous factors that vary by source – including water availability, pressure and price. The temperature variation of groundwater abstraction pipes at residential properties was recorded and analysed as part of this study in order to estimate values for three model inputs, namely, pumping event duration, irrigation frequency, and flow rate. This research incorporates a basic end-use model for garden irrigation, with inputs derived from the case study in Cape Town, South Africa. The model was subsequently used to stochastically evaluate garden irrigation. Over an 11-d period, 68 garden irrigation events were identified in the sample group of 10 residential properties. The average garden irrigation event duration was 2 h 16 min and the average daily garden irrigation event volume was 1.39 m 3 .